THE EFFECT OF EXPERIMENT LEARNING METHOD ON STUDENTS’ PROCESS SKILL OF VIII CLASS ON THE MOVEMENT PLANT MATERIAL - 'Aini, Kurratul; Samiha, Yulia Tri; Sunarti, Riri Novita; Azizi, Nurul (Al 'Ilmi : Jurnal Pendidikan MIPA, 2015)
The purpose of this study was to determine the effect of experimental teaching methods on the skills of science process students in class VIII MTs in OKI District. This research uses non-equivalent control group design design with quasi-experiment method. The sample of research is 68 students. Based on the result of research, students' science process skill in the implementation of learning with experimental method is better than learning by demonstration method in control class. Based on the calculation of t test, obtained result 3,218. It shows H0 rejected and Ha accepted. Based on the gain test, the improvement of students' science process skill in the experimental class is 0,53 (mean) while the control class is 0,23 (low). Based on the results of this study can be concluded that the learning by experimental methods affect the improvement of students' science process skills on the plant movement system.Keywords: learning method, plant movement system, scientific process skill